Justice denied: how the Egyptian legal system perpetuates impunity - El Hosseiny, Salma Nasser (AUC Knowledge Fountain, 2013)
Retribution to the martyrs of the Revolution is one of the core demands of Egypt's 2011 Revolution. Almost three years later, this demand is yet to be fulfilled. The purpose of this paper is not to prove the existence of impunity in Egypt but rather to propose an analytical framework that can show how the Egyptian legal system perpetuates impunity. I examine two case studies: the Maspero massacre and Ramlat Boulaq protests. I argue that impunity is multi-dimensional, and accordingly I define two dimensions for analysis of the cases: strategic and structural dimensions of impunity. Strategic impunity is defined as ad-hoc measures taken by the authorities to derail processes of accountability or demands for truth and justice, and structural impunity is defined as inherent, structural traits of the legal system that prevent successful prosecutions of human rights violations. In the final chapter, I examine some measures taken by the authorities' for legislative and security sector reforms. Through this examination, I highlight their lack of political will to break the cycle of impunity. In contrast, I analyze a proposal made by the “Police for Egypt” initiative for security sector reform and transitional justice. I conclude that maintaining the Egyptian legal system as it is will continue to result in impunity for human rights violations.